Does Welfare Spending Crowd Out Charitable Activity? Evidence from Historical England under the Poor Laws - Nina Boberg-Fazlic; Paul Sharp (European Historical Economics Society (EHES), 2013)
This paper examines the relationship between government spending and charitable activity. We present a novel way of testing the 'crowding out hypothesis', making use of the fact that welfare provision under the Old Poor Laws was decided on the parish level, thus giving the heterogeneity we need to test for the impact of different levels of welfare support within a single country. Using data on poor relief spending combined with data on charitable incomes by county for two years before and after 1800, we find a positive relationship: areas with more public provision also enjoyed higher levels of charitable income. These results are confirmed when instrumenting for Poor Law spending using the distance to London and historical migration to London, as well as when looking at first differences.
Keywords: H5; I3; N3; 330; Charity; crowding out hypothesis; England; Poor Laws